Personalized education and its role in reducing dropout student rates in Colombia: The CESA case (2014)
In Colombia the dropout rate in 2013 among business, economics and accounting schools was 53.65% at the national level. Is within this context, that the Colegio de Estudios Superiores de Administración (CESA) reported one of the lowest dropout rates at the national level. From an institutional point of view it was important to identify the key factors and determinants that led to the reduction of the dropout rate among the student body. We analyze the management practices of the institution towards personalized education from a hermeneutic perspective using the Hutchens model. The subsequent analysis allows us to identify the key factors and determinants that led to the reduction of the dropout rate at CESA.